The graduate record examination and Master of Public Administration programs - Bowman, J.S.
The Graduate Record Examination is probably the most celebrated and controversial element of all entrance requirements to graduate school. Yet little is known about how test scores are used. This study reports the findings from a national survey of Master of Public Administration programs. Following a discussion dealing with the evolution of and literature on standardized testing, the extent, rationale, and role of the test admissions procedures are explored. The analysis closes with a brief commentary on the part that objective examinations can play in public administration programms. Reproduced
Keywords: U.S.A; Master of Public Administration; Public Administration - Study and Teaching - U.S.A.